Virus-specific memory T cells populate tumors and can be repurposed for tumor immunotherapy - Rosato, Pamela C. (Nat Commun, 2019)
The immunosuppressive tumor microenvironment limits the success of current immunotherapies. The host retains memory T cells specific for previous infections throughout the entire body that are capable of executing potent and immediate immunostimulatory functions. Here we show that virus-specific memory T cells extend their surveillance to mouse and human tumors. Reactivating these antiviral T cells can arrest growth of checkpoint blockade-resistant and poorly immunogenic tumors in mice after injecting adjuvant-free non-replicating viral peptides into tumors. Peptide mimics a viral reinfection event to memory CD8+ T cells, triggering antigen presentation and cytotoxic pathways within the tumor, activating dendritic cells and natural killer cells, and recruiting the adaptive immune system. Viral peptide treatment of ex vivo human tumors recapitulates immune activation gene expression profiles observed in mice. Lastly, peptide therapy renders resistant mouse tumors susceptible to PD-L1 blockade. Thus, re-stimulating known antiviral immunity may provide a unique therapeutic approach for cancer immunotherapy.